PENGARUH SISTEM INFORMASI AKUNTANSI PENJUALAN DAN PENGENDALIAN INTERNAL TERHADAP EFEKTIVITAS PENGENDALIAN PIUTANG PADA WISATA KEBUN JERUK SIOMPU DESA KAEMBULAWA - Hesti Saras Wati; Moh. Amin; Siti Aminah Anwar (Universitas Islam Malang, 2022)
Processing title “the effect of the notification device on the principle of selling or internal management on the effectiveness of credit management in siompu citrus orchard tourism, kaembulawa village” the results of this processing lead to the knowledge of notification analysis, which includes selling or internal management regarding the effectiveness of claims management in the siompu citrus orchard, kaembulawa village. The population of this processing consists of 30 staff who are engaged in tourism in the siompu orange garden in the village of kaembulawa with a sample of 30 person. The data various for that study is data primary. The method analysis data uses this method that a method quantitative using statistics descriptive, testing normality, testing classically hypotheses, multiple regression linear analysis, or test hypotheses. From a results that survey, the processing of notification of selling activities significantly affect the effectiveness of accounts receivable management something a than 0.05 (0.025% < 0.05), internal or management there is something sure about effectiveness something claims. Manager. Bring. Significant percentage less than 0.05 (0.41 < 0.05). assessment coefficient something determination is 0,408 and 40,8%. it when that a presentation something notifications including selling or internal management if effectiveness something debt management is 40,8% the only one 59.2% affects another variable that is not included in this survey. Keywords: selling activity information tool, control internal, debt management